Pyroligneous Acid as a Natural Preservative for Clonal Material of Eucalyptus Wood - Thatiele Pereira Eufrazio de Moraes; Raquel Marchesan; Karolayne Ferreira Saraiva; Vanessa Coelho Almeida; Luiz Fernandes Silva Dionísio; Rodrigo Araújo Fortes; Adriano Guimarães Carvalho; Cristiano Bueno de Moraes; Danival José de Souza (Floresta e Ambiente)
Abstract This study aimed to determine the resistance of Eucalyptus wood clones after exposure to the soil in a decay field. Samples taken from the heartwood of 3 Eucalyptus camaldulensis x Eucalyptus grandis hybrid trees were used for the pyroligneous liquor, chromated copper borat, and untreated treatments, where physical, chemical, and mechanical tests were used for evaluation. Chemical and mechanical analysis demonstrated that there was interaction between factors and significant differences between and within treatments. Wood treated with pyroligneous liquor showed lower solubility in cold water when compared to CCB and, therefore, lower leaching. Both treatments were statistically equal in terms of MOR resistance and mass loss. It was concluded that treating Eucalyptus wood with pyroligneous acid, compared to treatment with CCB and untreated wood, was equally efficient mainly for the property of resistance to static bending, showing potential as a preservative product.